Real-time quantitative PCR of Salmonella spp. and Escherichia coli in fresh produce from Korean and Philippine markets - Dimasupil, Ma. Angela Z. (Institute of Biology, College of Science, University of the Philippines Diliman, 2013)
Molecular methods are increasingly being developed for the detection and qualification of microorganisms associated with food. In this study, simple, rapid and specific real-time quantitative PCR (RT-qPCR) assays to quantify Salmonella spp. and Escherichia coli in fresh produce were applied and confirmed by targeting the invA and uidA genes, respectively. The assays were validated by application in spiked and naturally-contaminated fresh produce samples and quantification limits were 3 and 4 log CFU/ml for Salmonella spp. and E.coli, respectively. Spiking assays in various fresh produce generated reliable and reproducible quantification data shown in the comparison of the counts from direct plating and RT-qPCR methods.Detection was also possible in 1log CFU/ml of Salmonella spp. without the need for enrichment.The direct RT-qPCR method can confirm a positive result within a day and is less tedious compared to traditional culture methods for quantification and can be useful in routine food analysis and detection of pathogens during outbreaks. Incidence of bacterial contamination in leafy vegetables from local markets in Gwangju, South Korea and fruits in Quezon City, Philippines was also investiated. Out of 13 samples,9 (6.5%) were positive for Salmonella spp. and 55 (39.6%) for E. coli.The type of markets, packaging, and processing that may affect produce quality were evaluated. The results illustrate the importance of proper processing, handling and storage of fresh produce to prevent the risk for foodborne diseasese